The value of community-integrated health information exchanges: three recent examples from El Paso, Texas. (26th September 2022) - Sloan-Aagard, Chantel; Helgesen, Wanda; Nañez, Juan; Law, Jon; Currey, J C; Meils, Jacob; Bishop, Joel; Hartmann, Emily
Abstract: The foundational role of health information exchanges (HIEs) is to facilitate communication between clinical partners in real time. Once this infrastructure for the secure and immediate flow of patient information is built, however, HIEs can benefit community public health and clinical care in myriad other ways that are in line with their mission, goals, patient privacy, and funding structures. We encourage the development of community-integrated HIEs and list specific steps that can be taken toward community integration. We give three examples of those steps in action from a community HIE in El Paso, TX. Each local partnership, in combination with technology innovation, resulted in the development of informatics tools to address community health needs and generated long-term benefits, especially for the most vulnerable patients. Two examples relate to different aspects of the COVID-19 pandemic and a third to the Afghan refugee evacuation.